Investment decisions and profitability analysis of Al-Arafah Islami Bank Limited - Chowdhury, Nusrat Jahan (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.